2006
DOI: 10.1093/brain/awl236
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar damage impairs detection of somatosensory input changes. A somatosensory mismatch-negativity study

Abstract: Several recent studies support the view that the cerebellum's contribution to sensory processing is not limited to movement regulation. In a previous paper (Restuccia D, Valeriani M, Barba C, Le Pera D, Capecci M, Filippini V, Molinari M. Functional changes of the primary somatosensory cortex in patients with unilateral cerebellar lesions. Brain 2001; 124: 757-68) we showed that the cerebellum influences somatosensory input processing at very early stages. The present study was aimed at verifying whether an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
127
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 67 publications
14
127
1
Order By: Relevance
“…For instance, the two imaging studies that have reported cerebellar activation in an auditory duration MMN task used a fixed SOA (Dittmann-Balçar et al, 2001;Schall et al, 2003). A fixed SOA was also used in a study showing a diminished somatosensory MMN in patients with unilateral cerebellar damage (Restuccia et al, 2007). The present results suggest that these effects might be related to the periodicity of the stimuli.…”
Section: Mismatch Negativity -Periodicitymentioning
confidence: 59%
See 1 more Smart Citation
“…For instance, the two imaging studies that have reported cerebellar activation in an auditory duration MMN task used a fixed SOA (Dittmann-Balçar et al, 2001;Schall et al, 2003). A fixed SOA was also used in a study showing a diminished somatosensory MMN in patients with unilateral cerebellar damage (Restuccia et al, 2007). The present results suggest that these effects might be related to the periodicity of the stimuli.…”
Section: Mismatch Negativity -Periodicitymentioning
confidence: 59%
“…In humans, two imaging studies have reported cerebellar activation in duration MMN paradigms (Dittman-Balçar et al, 2001;Schall et al, 2003). One patient study reported a diminished somatosensory mismatch response to deviant tactile stimuli applied to the affected (ipsilesional) hand of patients with unilateral cerebellar lesions compared to stimuli applied to the unaffected hand (Restuccia et al, 2007). In contrast, two of the patients showed normal MMN responses on an auditory task using a pitch deviant.…”
Section: Introductionmentioning
confidence: 99%
“…Restuccia et al (2007) concluded the cerebellum plays a role in pre-attentive detection of novel or deviant somatosensory stimuli, though consistent sensory impairment has not demonstrated with cerebellar impairments. Restuccia et al (2007) found reports of weight discrimination and kinaesthesia impairments as well as sensory dysgraphia resulting from cerebellar impairments. Further studies to understand the role the cerebellum plays and the impact of cerebellar lesions on somatosensory processing are needed.…”
Section: Cerebellar Involvement In Sensory Processingmentioning
confidence: 99%
“…The cerebellum also has an influence on inhibitory circuits in the S-I and may modulate receptive fields and hence optimise cutaneous discrimination (Restuccia et al, 2007). Restuccia et al (2007) concluded the cerebellum plays a role in pre-attentive detection of novel or deviant somatosensory stimuli, though consistent sensory impairment has not demonstrated with cerebellar impairments. Restuccia et al (2007) found reports of weight discrimination and kinaesthesia impairments as well as sensory dysgraphia resulting from cerebellar impairments.…”
Section: Cerebellar Involvement In Sensory Processingmentioning
confidence: 99%
See 1 more Smart Citation